Philip F. Thomas correspondence and speech - Thomas, Philip F. (Philip Francis), 1810-1890.
Speech (1877 February 28; House of Representatives) by Thomas concerning constitutional provisions for the election of the president and vice president of the United States; and letters (1895 March) from several of Thomas's colleagues in response to inquiries by Worthington Chauncey Ford regarding Thomas's departure from his post as U.S. secretary of the treasury in 1861.
U.S. representative from and governor of Maryland, U.S. secretary of the treasury, and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ford, Worthington Chauncey, -- 1858-1941.; United States. -- Congress. -- House; United States. -- Department of the Treasury; Election law -- United States; Presidents -- United States -- Election; Vice-Presidents -- United States -- Election; United States -- Politics and government -- 1849-1877.; Cabinet officers; Governors -- Maryland; Lawyers; Public officials -- Maryland; Representatives, U.S. Congress -- Maryland